Method Research of Coal Mine Roof Strain Detection Based on the Fiber Bragg Grating Sensor with Thermodynamic Couple Numerical Condition. (3rd August 2017) - Jian, Zhang; Chuan, Lu; De-Shu, Lin
Abstract : In order to solve the problem that the measure precision of coal roof rock strain amount detection using traditional electric sensor is insufficient, a kind of High Sensitive Surface-Pasted Fiber Bragg Grating Strain Sensor based on rock bolting is designed for substitution. Furthermore, a kind of Reference Grating Zero-Strain method based on sensitivity matrix coefficient is proposed for solving FBG strain-temperature cross-sensitivity problem and realizing the better separation relevant to strain and temperature. It is proved that the sensitivity and measurement precision and anti-interference ability of FBG strain sensors are better than traditional electricity class sensors, being able to realize the real-time and online detection for coal roof surrounding rock strain.